Performance Allowance Factors on the Performance of ASN Employees at Health CenterX in Gresik - Heru Baskoro; Elok Vilantika; Sukaris Sukaris; Nur Cahyadi (Universitas Muhammadiyah Gresik, 2022)
This study aims to analyze the performance allowance factor on employee performance, especially at ASN Helath Center X in Gresik. The health center has provided performance allowances, but employees work not optimally seen from work productivity and work discipline which have not experienced significant changes and tend to remain. The approach used is quantitative descriptive analysis with explanatory research. The population is all employees of the Helath Center, totaling 60 people, then sample selection using purposive sampling is carried out so that 36 people are obtained. The data used is primary data obtained directly collected by questionnaire. This study uses a Likert scale of 1 to 5 for the measurement of research variables. Data analysis used instrument test and simple linear regression. The results showed that the performance allowance had a positive and significant effect on the performance of ASN employees at Helath Center X in Gresik. The existence of performance allowances causes employees to be motivated to work optimally so that it affects the performance of employees at the agency.